After Papua New Guinea's Resource Boom: Is the Kina Overvalued?. Issue 1 (22nd November 2017) - Fox, Rohan; Schröder, Marcel
Abstract: Papua New Guinea's (PNG) resource boom has come to an end. Theory suggests that the real exchange rate (RER) should subsequently depreciate in order to restore internal and external balance. In practice, however, the imposition of foreign exchange controls has led to a large backlog in foreign currency orders suggesting that the RER is significantly overvalued. The purpose of this paper is to inform the ongoing policy debate surrounding this issue by estimating the extent to which PNG's RER is currently misaligned. Our results suggest that the kina should depreciate by about 20% to close the gap between the actual and equilibrium value of the RER. Otherwise PNG is likely to pay high economic costs as real overvaluation sustained through foreign exchange restrictions led to resource misallocation, lower economic growth, black markets, and ultimately a balance of payments crisis in many other developing countries in the past.